Clinical Features and Serological Markers Risk Model Predicts Overall Survival in Patients Undergoing Breast Cancer and Bone Metastasis Surgeries - Mou, Haochen; Wang, Zhan; Zhang, Wenkan; Li, Guoqi; Zhou, Hao; Yinwang, Eloy; Wang, Fangqian; Sun, Hangxiang; Xue, Yucheng; Wang, Zenan; Chen, Tao; Chai, Xupeng; et al. (Frontiers in Oncology, 2021)
Background Surgical therapy of breast cancer (BC) and bone metastasis can effectively improve the prognosis of breast cancer. However, after the first operation, the relationship between preoperative indicators and outcomes in patients who underwent metastatic bone surgery remained to be studied. Purpose 1. Recognize clinical and laboratory prognosis factors available to clinical doctors before the operation for bone metastatic breast cancer patients. 2. Develop a risk prediction model for 3-year postoperative survival in patients with breast cancer bone metastasis. Methods From 2014 to 2020, patients suffered from BC bone metastasis and received therapeutic procedures in our institution were included for analyses (n=145). For patients who underwent both BC radical surgery and bone metastasis surgery, comprehensive datasets of the parameters of interest (clinical features, laboratory factors, and patient prognoses) were collected (n=69). We performed Multivariate Cox regression to identify factors which were associated with postoperative outcome. 3-year survival prediction model and nomograms were established by 100 bootstrapping. Its benefit was evaluated by calibration plot, C-index, and decision curve analysis. Results Radiotherapy for primary cancer (hazard ratio [HR], 3.02; confidence interval [CI], 1.14-8.01, p=0.027), pathological type of metastatic BC (HR, 2.1; CI,1.4-3.2, p＜0.001), lymph node metastasis (HR, 2.80; CI, 1.08-7.22; p=0.034), elevated serum alanine aminotransferase (ALP) (HR, 1.005; CI, 1.001-1.008; p=0.009), lactate dehydrogenase (LDH) (HR, 1.007; CI, 1.002-1.012; p=0.003) were associated with postoperative prognosis. Pathological type of metastatic BC (HR, 1.65; CI, 1.11-2.46, p=0.014), multiple bone metastasis (HR, 2.94; CI, 1.08-8.01, p=0.035), organ metastases (HR, 3.75; CI, 1.69-8.32, p=0.001), and elevated serum LDH (HR, 1.005; CI, 1.001-1.009, p=0.017) were associated with 3-year survival. Then those significant variables and serum ALP counts were integrated to construct nomograms for 3-year survival. The C-statistic of the established predictive model was 0.83(95% CI 0.56-1). The calibration plot presents a graphical representation of calibration. In the decision curve analysis, the benefits are higher than those of the extreme curve. Conclusion In spite of the hazard factors for early death need to be confirmed by prospective researches, non-operative therapy or close monitoring after surgery should be considered for high-risk preoperative patients. Level of evidence Level III, prognostic study.